Recent Advance in Iminyl Radical Triggered C–H and C–C Bond Functionalization of Oxime Esters via 1,5-HAT and β-Carbon Scission - Liu, Le; Duan, Xin-Hua; Guo, Li-Na (Synthesis, 2021)
The direct functionalization of C(sp3)–H and C(sp3)–C(sp3) bonds is considered as one of the most valuable synthetic strategies because of its high efficiency and step-economy for the rapid assembly of complex molecules. However, the relatively high bond disassociation energies (BDEs) and similar chemical environment lead to large obstacles in terms of low reactivity and selectivity. Using a radical-based strategy has proved to be an efficient approach to overcome these difficulties via a hydrogen atom transfer (HAT) process for selective C(sp3)–H functionalization and β-carbon scission for C(sp3)–C(sp3) bond derivatization. Oxime esters have emerged as outstanding precursors of iminyl radicals for versatile chemical transformations. This short review summaries the recent advances in site-specific C(sp3)–H functionalization and C(sp3)–C(sp3) bond cleavage starting from oxime esters by our group and pioneering work by others, mainly focusing on the reaction design as well as the reaction mechanism.1 Introduction2 C(sp3)–H Bond Functionalization via 1,5-HAT of Acyclic Oxime Esters2.1 1,5-HAT/Cyclization2.2 1,5-HAT/C–C or C–Heteroatom Bond Formation3 C(sp3)–C(sp3) Bond Functionalization via β-Carbon Scission of Cyclic Oxime Esters3.1 β-Carbon Scission/C–C or C–Heteroatom Bond Formation3.2 β-Carbon Scission/Cyclization4 Conclusion and Outlook
Keywords: iminyl radical; oxime esters; 1,5-hydrogen atom transfer; β-carbon scission; C(sp3)–H functionalization; C(sp3)–C(sp3) functionalization